Developing a User-Centered Digital Platform to Enhance Sustainable Marketing of Fisheries Products - Dimas Bayu Sasongko; Jefri Putri Nugraha; Dewi Alima Nostalia Suseno; R. Sugeng Rahardjo; Djoko Surahmat; Prayoto Prayoto; Bambang Supriyadi; Sri Wartini (Jurnal Ilmiah Manajemen Kesatuan, 2025)
With the increasing importance of digital marketing in the fisheries sector, the study investigates user needs and key features for a platform that supports efficient and sustainable product promotion. This study explores the development of a digital platform designed to enhance the marketing of fisheries products. The research employs a mixed-methods approach, combining qualitative design-based research with quantitative usability testing. Data collection was done through interviews, focus groups, and surveys with stakeholders, including business unit managers and consumers. The results identify essential platform features such as easy navigation, product information transparency, social media integration, and secure payment systems. The findings also highlight the importance of user-centered design principles in developing a digital platform that aligns with users' needs and enhances their experience. The study contributes to understanding how digital solutions can transform fisheries product marketing, offering practical implications for the development of similar platforms in other sectors. Future research should focus on real-world testing and the scalability of such platforms across various markets.